An algorithm for evaluating the linear redundancy and the factor of inertial groups of S-box - Nguyen, Nghi Van (Journal of Science and Technology on Information security, 2020)
Abstract— This paper presents an algorithm for evaluating the linear redundancy and the factor of inertial groups with small computational complexity. Specifically, the article introduces the concept of the factor of inertial groups, the relationship between the factor of inertial groups and the linear redundancy of S-box. Thus, it is recommended to use S-boxes that do not possess linear redundancy and have the factor of inertial groups equal to 1 to have better cryptographic properties, and also provide an algorithm for searching such large size S-boxes. Tóm tắt— Bài viết này đưa ra thuật toán đánh giá độ dư thừa tuyến tính và hệ số quán tính của S-hộp với độ phức tạp tính toán nhỏ. Khái niệm hệ số quán tính, mối liên quan giữa hệ số nhóm quán tính và độ dư thừa tuyến tính của S-hộp được phân tích cụ thể. Qua đó, đưa ra khuyến nghị nên sử dụng các S-hộp không sở hữu độ dư thừa tuyến tính và có hệ số quán tính bằng 1 để có tính chất mật mã tốt hơn, đồng thời cũng đưa ra thuật toán để tìm các S-hộp kích thước lớn như vậy.